Competing Narratives in a Case Biography: A Tale of Two Citadels. (15th July 2020) - Jones, Caroline; Montgomery, Jonathan
Abstract: This article is the fourth in a series introducing the reader to methods and theories relevant to advancing socio‐legal research. They are written for the curious rather than the expert reader and provide illustrations of how the theories, methods, and frameworks have been employed and might be used in your work. This article explores the use of case biography methods for socio‐legal studies. Drawing on 'paths to justice' studies, network analysis, and legal archaeology, we develop a case study of AC v. Berkshire West Primary Care Trust . We show how the judicial determination of the case suppressed a transgender rights narrative construction of the dispute in favour of one about health care law. Our case biography analysis explores how competing narratives can be traced not only through legal argument and literature, but also through the personnel involved, in ways that are obscured by formal records. Paying attention to biographical features leads to a richer understanding of cases, including the importance of pre‐ and post‐judicial decision‐making aspects.